Missed Opportunities: Evolution of Patients Leaving without Being Seen or against Medical Advice during a Six-Year Period in a Swiss Tertiary Hospital Emergency Department. (12th June 2014) - Carron, Pierre-Nicolas; Yersin, Bertrand; Trueb, Lionel; Gonin, Philippe; Hugli, Olivier
Abstract : Aim. The study aimed at describing the evolution over a 6-year period of patients leaving the emergency department (ED) before being seen ("left without being seen" or LWBS) or against medical advice ("left against medical advice" or LAMA) and at describing their characteristics. Methods. A retrospective database analysis of all adult patients who are admitted to the ED, between 2005 and 2010, and who left before being evaluated or against medical advice, in a tertiary university hospital. Results. During the study period, among the 307, 716 patients who were registered in the ED, 1, 157 LWBS (0.4%) and 1, 853 LAMA (0.9%) patients were identified. These proportions remained stable over the period. The patients had an average age of 38.5 ± 15.9 years for LWBS and 41.9 ± 17.4 years for LAMA. The median time spent in the ED before leaving was 102.4 minutes for the LWBS patients and 226 minutes for LAMA patients. The most frequent reason for LAMA was related to the excessive length of stay. Conclusion. The rates of LWBS and LAMA patients were low and remained stable. The patients shared similar characteristics and reasons for leaving were largely related to the length of stay or waiting time.